Cultural tourism and community engagement: Insight from Montenegro - Ilija Moric; Sanja Pekovic; Jovana Janinovic; urica Perovic; Michaela Griesbeck (Business Systems Research (BSR), 2021)
Background: Cultural tourism in Montenegro is growing, mostly due to the integral growth and development of tourism products. However, an in-depth insight into the relationship between cultural tourism and community engagement is missing. Objectives: The paper aims to examine the relationship between cultural tourism development and community engagement in Montenegro. Methods/Approach: Using the extensive literature, available secondary data, and an analysis of relevant policies, the paper explores new possibilities for diversifying tourism offer at heritage sites, by engaging volunteers, enhancing understanding of the socio-historical background, promoting the usage of digital tools, partnering with relevant stakeholders, introducing innovative funding tools and schemes. Results: Several management issues associated with heritage tourism and community participation are acknowledged. Conclusions: Key findings indicate the need for a systemic, dynamic, and innovative framework for sustainable and highly impactful heritage tourism in Montenegro, which policymakers, heritage ventures, and other stakeholders might use to strengthen community engagement and development at the heritage sites.
Keywords: M21; 330; cultural tourism; heritage; community engagement; Montenegro